CN113772664B - Nickel black-graphene composite photo-thermal conversion film and preparation method thereof - Google Patents
Nickel black-graphene composite photo-thermal conversion film and preparation method thereof Download PDFInfo
- Publication number
- CN113772664B CN113772664B CN202111047273.8A CN202111047273A CN113772664B CN 113772664 B CN113772664 B CN 113772664B CN 202111047273 A CN202111047273 A CN 202111047273A CN 113772664 B CN113772664 B CN 113772664B
- Authority
- CN
- China
- Prior art keywords
- nickel
- graphene
- black
- conversion film
- light
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Active
Links
Images
Classifications
-
- C—CHEMISTRY; METALLURGY
- C01—INORGANIC CHEMISTRY
- C01B—NON-METALLIC ELEMENTS; COMPOUNDS THEREOF; METALLOIDS OR COMPOUNDS THEREOF NOT COVERED BY SUBCLASS C01C
- C01B32/00—Carbon; Compounds thereof
- C01B32/15—Nano-sized carbon materials
- C01B32/182—Graphene
- C01B32/184—Preparation
- C01B32/19—Preparation by exfoliation
-
- C—CHEMISTRY; METALLURGY
- C02—TREATMENT OF WATER, WASTE WATER, SEWAGE, OR SLUDGE
- C02F—TREATMENT OF WATER, WASTE WATER, SEWAGE, OR SLUDGE
- C02F1/00—Treatment of water, waste water, or sewage
- C02F1/44—Treatment of water, waste water, or sewage by dialysis, osmosis or reverse osmosis
- C02F1/447—Treatment of water, waste water, or sewage by dialysis, osmosis or reverse osmosis by membrane distillation
-
- C—CHEMISTRY; METALLURGY
- C25—ELECTROLYTIC OR ELECTROPHORETIC PROCESSES; APPARATUS THEREFOR
- C25C—PROCESSES FOR THE ELECTROLYTIC PRODUCTION, RECOVERY OR REFINING OF METALS; APPARATUS THEREFOR
- C25C1/00—Electrolytic production, recovery or refining of metals by electrolysis of solutions
- C25C1/06—Electrolytic production, recovery or refining of metals by electrolysis of solutions or iron group metals, refractory metals or manganese
- C25C1/08—Electrolytic production, recovery or refining of metals by electrolysis of solutions or iron group metals, refractory metals or manganese of nickel or cobalt
-
- C—CHEMISTRY; METALLURGY
- C25—ELECTROLYTIC OR ELECTROPHORETIC PROCESSES; APPARATUS THEREFOR
- C25C—PROCESSES FOR THE ELECTROLYTIC PRODUCTION, RECOVERY OR REFINING OF METALS; APPARATUS THEREFOR
- C25C7/00—Constructional parts, or assemblies thereof, of cells; Servicing or operating of cells
- C25C7/02—Electrodes; Connections thereof
-
- C—CHEMISTRY; METALLURGY
- C25—ELECTROLYTIC OR ELECTROPHORETIC PROCESSES; APPARATUS THEREFOR
- C25C—PROCESSES FOR THE ELECTROLYTIC PRODUCTION, RECOVERY OR REFINING OF METALS; APPARATUS THEREFOR
- C25C7/00—Constructional parts, or assemblies thereof, of cells; Servicing or operating of cells
- C25C7/06—Operating or servicing
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02A—TECHNOLOGIES FOR ADAPTATION TO CLIMATE CHANGE
- Y02A20/00—Water conservation; Efficient water supply; Efficient water use
- Y02A20/124—Water desalination
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02A—TECHNOLOGIES FOR ADAPTATION TO CLIMATE CHANGE
- Y02A20/00—Water conservation; Efficient water supply; Efficient water use
- Y02A20/124—Water desalination
- Y02A20/131—Reverse-osmosis
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02A—TECHNOLOGIES FOR ADAPTATION TO CLIMATE CHANGE
- Y02A20/00—Water conservation; Efficient water supply; Efficient water use
- Y02A20/124—Water desalination
- Y02A20/138—Water desalination using renewable energy
- Y02A20/142—Solar thermal; Photovoltaics
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02A—TECHNOLOGIES FOR ADAPTATION TO CLIMATE CHANGE
- Y02A20/00—Water conservation; Efficient water supply; Efficient water use
- Y02A20/20—Controlling water pollution; Waste water treatment
- Y02A20/208—Off-grid powered water treatment
- Y02A20/212—Solar-powered wastewater sewage treatment, e.g. spray evaporation
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02P—CLIMATE CHANGE MITIGATION TECHNOLOGIES IN THE PRODUCTION OR PROCESSING OF GOODS
- Y02P20/00—Technologies relating to chemical industry
- Y02P20/10—Process efficiency
Landscapes
- Chemical & Material Sciences (AREA)
- Organic Chemistry (AREA)
- Engineering & Computer Science (AREA)
- Materials Engineering (AREA)
- Electrochemistry (AREA)
- Metallurgy (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Nanotechnology (AREA)
- Inorganic Chemistry (AREA)
- Life Sciences & Earth Sciences (AREA)
- Hydrology & Water Resources (AREA)
- Environmental & Geological Engineering (AREA)
- Water Supply & Treatment (AREA)
- Carbon And Carbon Compounds (AREA)
Abstract
一种镍黑‑石墨烯复合光热转换膜及其制备方法,涉及镍黑‑石墨烯复合光热转换膜的结构、制备及海水淡化应用。采用一步电化学方法将石墨烯与镍黑同时沉积在泡沫镍孔壁面,得到镍黑‑石墨烯复合光热转换膜。协同金属镍黑的等离子体共振效应与石墨烯碳材料对光吸收波长范围广的优点,提高光热转化效率。在光照条件下镍黑‑石墨烯光热转换膜用于海水淡化。1sun光照强度下,光‑蒸汽能量转化效率达162.4%,蒸汽渗透率可达2.37kg/m2·h。
A nickel black-graphene composite light-to-heat conversion film and a preparation method thereof relate to the structure, preparation and seawater desalination application of the nickel black-graphene composite light-to-heat conversion film. A one-step electrochemical method is used to simultaneously deposit graphene and nickel black on the wall of nickel foam pores to obtain a nickel black-graphene composite light-to-heat conversion film. The plasmon resonance effect of metal nickel black and the advantages of graphene carbon materials in a wide range of light absorption wavelengths can be used to improve the light-to-heat conversion efficiency. Nickel black-graphene light-to-heat conversion film for seawater desalination under light conditions. Under the light intensity of 1 sun, the light-steam energy conversion efficiency can reach 162.4%, and the steam permeability can reach 2.37kg/m 2 ·h.
Description
技术领域technical field
本发明属于光热转换领域,及其在海水淡化方面的应用。The invention belongs to the field of photothermal conversion and its application in seawater desalination.
背景技术Background technique
淡水资源是人类生存不可或缺的资源。因此,越来越多的国家采用海水淡化技术来缓解淡水短缺。然而,在海水淡化过程中需要较高的能量消耗。太阳能作为生物生存所必需的能源,在生活中无处不在,取之不尽,人们常认为将其引入海水淡化技术中,具有光热转换作用,有效降低能源消耗。通过结合地球上两种最丰富的的资源,实现海水淡化解决水资源短缺问题,实现可持续发展,是未来海水淡化技术的发展大趋势。目前,常用的太阳能热转换材料主要分为以下几类:各种碳材料、等离子金属、无机半导体和有机聚合物。等离子金属材料由于其强大的电磁波吸收能力而被用作太阳能吸收材料。目前,金银等贵金属已得到广泛研究,但其高成本严重限制了其广泛应用。经济实惠的镍黑可以有效替代昂贵的太阳能热转换材料,实现太阳能热转换。与此同时,石墨烯是一种新兴二维材料,具有太阳能吸收波长范围广,光热转换性能好等特点,被广泛应用于光热转换。因此,本发明考虑将镍黑材料与石墨烯结合到一起形成光热复合材料并应用在海水淡化技术方面。Fresh water is an indispensable resource for human survival. Therefore, more and more countries adopt seawater desalination technology to alleviate the shortage of fresh water. However, high energy consumption is required in the desalination process. Solar energy, as an energy necessary for the survival of organisms, is ubiquitous and inexhaustible in life. People often think that the introduction of solar energy into seawater desalination technology has the effect of light-to-heat conversion and can effectively reduce energy consumption. By combining the two most abundant resources on the earth, seawater desalination can solve the problem of water shortage and achieve sustainable development, which is the general trend of seawater desalination technology in the future. At present, the commonly used solar thermal conversion materials are mainly divided into the following categories: various carbon materials, plasmonic metals, inorganic semiconductors, and organic polymers. Plasmonic metal materials have been used as solar energy absorbing materials due to their strong electromagnetic wave absorption ability. At present, precious metals such as gold and silver have been widely studied, but their high cost severely limits their wide application. Affordable nickel black can effectively replace expensive solar thermal conversion materials to achieve solar thermal conversion. At the same time, graphene is an emerging two-dimensional material, which has the characteristics of a wide range of solar absorption wavelengths and good photothermal conversion performance, and is widely used in photothermal conversion. Therefore, the present invention considers combining nickel black material and graphene to form a photothermal composite material and applying it in seawater desalination technology.
发明内容Contents of the invention
本发明的目的在于提供一种镍黑-石墨烯复合光热转换膜及其制备方法,旨在通过协同发挥金属材料与碳材料在光热转换方面的优点,从而提高光热转换效率及海水淡化作用。The purpose of the present invention is to provide a nickel black-graphene composite light-to-heat conversion film and its preparation method, aiming to improve the light-to-heat conversion efficiency and seawater desalination by synergistically utilizing the advantages of metal materials and carbon materials in light-to-heat conversion effect.
本发明步骤是:The steps of the present invention are:
一种镍黑-石墨烯复合光热转换膜及其制备方法,其特征在于具体步骤为:A nickel black-graphene composite light-to-heat conversion film and a preparation method thereof, characterized in that the specific steps are:
(1)将一定量的硫酸铵与硫酸镍加入溶剂中,持续搅拌至充分溶解,形成电解液;(1) Add a certain amount of ammonium sulfate and nickel sulfate into the solvent, and keep stirring until fully dissolved to form an electrolyte;
(2)泡沫镍为阴极,石墨箔为阳极,电解液中调整电极距离;(2) Nickel foam is used as the cathode, graphite foil is used as the anode, and the electrode distance is adjusted in the electrolyte;
(3)一定直流电压下,电解液产生的气体及羟基自由基对石墨箔产生插层作用,从而剥离出石墨烯;镍离子起到载体作用,将石墨烯转移到阴极上的同时,本身还原为镍黑;从而在阴极上生成均匀的镍黑-石墨烯复合膜;(3) Under a certain DC voltage, the gas and hydroxyl radicals generated by the electrolyte intercalate the graphite foil, thereby peeling off the graphene; the nickel ions act as a carrier, transferring the graphene to the cathode while reducing itself Be nickel black; thereby generate uniform nickel black-graphene composite film on the cathode;
(4)调整电解液浓度、沉积电压及沉积时间以控制阴极上镍黑-石墨烯复合材料的含量;(4) Adjust the electrolyte concentration, deposition voltage and deposition time to control the content of nickel black-graphene composite material on the cathode;
所述步骤(1)中硫酸铵浓度为0~0.2 M,硫酸镍浓度为0~0.08 M;In the step (1), the concentration of ammonium sulfate is 0-0.2 M, and the concentration of nickel sulfate is 0-0.08 M;
所述步骤(2)中电极距离为0.5~2 cm;The electrode distance in the step (2) is 0.5-2 cm;
所述步骤(3)中电压范围为5~15 V;The voltage range in the step (3) is 5-15 V;
所述步骤(4)中沉积时间为5~40 min;The deposition time in the step (4) is 5-40 min;
(5)电沉积一定时间后,镍黑-石墨烯光热转换膜在去离子水中充分清洗,取出后60℃烘箱烘干12小时。(5) After a certain period of electrodeposition, the nickel black-graphene light-to-heat conversion film was fully washed in deionized water, and dried in an oven at 60°C for 12 hours after taking it out.
一种镍黑-石墨烯复合光热转换膜的形成原理:体系通电后,电解液产生的气体及羟基自由基对石墨箔产生插层作用,从而剥离出石墨烯。镍离子起到充电盐的作用,将石墨烯转移到阴极上的同时,本身还原为镍黑;从而在阴极上生成均匀的镍黑-石墨烯复合膜。The formation principle of a nickel black-graphene composite light-to-heat conversion film: After the system is energized, the gas and hydroxyl radicals generated by the electrolyte will intercalate the graphite foil, thereby peeling off the graphene. Nickel ions act as a charging salt, while transferring graphene to the cathode, it is reduced to nickel black itself; thus a uniform nickel black-graphene composite film is formed on the cathode.
本发明采用一步电化学法,制备过程简单,一次成膜;载体表面的镍黑在等离子体共振效应作用下可实现光热转换作用,石墨烯对光吸收波长范围广,协同作用以增加其在海水淡化过程中水蒸气的产生而获得更多淡水。The invention adopts a one-step electrochemical method, the preparation process is simple, and the film is formed at one time; the nickel black on the surface of the carrier can realize the photothermal conversion effect under the action of the plasma resonance effect, and the graphene has a wide range of light absorption wavelengths, and the synergistic effect increases its The production of water vapor in the desalination process to obtain more fresh water.
附图说明Description of drawings
附图1 镍黑-石墨烯复合光热转换膜的SEM图。Figure 1 SEM image of nickel black-graphene composite light-to-heat conversion film.
附图2 镍黑-石墨烯复合光热转换膜的XRD图。Figure 2 XRD pattern of nickel black-graphene composite light-to-heat conversion film.
附图3 镍黑-石墨烯复合光热转换膜的Raman图。Figure 3 Raman diagram of nickel black-graphene composite light-to-heat conversion film.
实施方式Implementation
为了更好地说明本发明,下面以镍黑-石墨烯复合光热转换膜为例结合附图对本发明进行进一步说明。In order to better illustrate the present invention, the present invention will be further described below by taking nickel black-graphene composite light-to-heat conversion film as an example in conjunction with the accompanying drawings.
实验前期准备:Pre-experiment preparation:
1. 镍黑-石墨烯复合光热转换膜的制备:1. Preparation of nickel black-graphene composite light-to-heat conversion film:
(1)将1.32g的硫酸铵和0.42g的硫酸镍加200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;(1) Add 1.32g of ammonium sulfate and 0.42g of nickel sulfate to 200ml of deionized water, and keep stirring at room temperature until fully dissolved to form an electrolyte solution;
(2)将泡沫镍接在阴极上,石墨箔接在阳极上,将接好的电极调整好距离并放入电解液中;(2) Connect the nickel foam to the cathode, connect the graphite foil to the anode, adjust the distance between the connected electrodes and put them into the electrolyte;
(3)打开外加直流电源的开关,调整实验电压及实验时间以调整泡沫镍上镍黑-石墨烯复合材料的含量;(3) Turn on the switch of the external DC power supply, adjust the experimental voltage and experimental time to adjust the content of the nickel black-graphene composite material on the foamed nickel;
(4)将镀好的镍黑-石墨烯光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。(4) Wash the plated nickel black-graphene light-to-heat conversion film in deionized water, take it out and dry it in an oven at 60°C for 12 hours.
图1图2和图3分别为镍黑-石墨烯复合光热转换膜的SEM、XRD和Raman图。通过SEM图可以清晰地看到石墨烯与镍黑在膜表面的存在,通过XRD和Raman 图可以看到镍与石墨烯的特征峰,可以有效证明镍黑-石墨烯复合膜被有效地制备了。Figure 1, Figure 2 and Figure 3 are the SEM, XRD and Raman diagrams of the nickel black-graphene composite light-to-heat conversion film, respectively. The existence of graphene and nickel black on the surface of the film can be clearly seen through the SEM image, and the characteristic peaks of nickel and graphene can be seen through the XRD and Raman images, which can effectively prove that the nickel black-graphene composite film is effectively prepared .
2. 实验过程:2. Experimental process:
将上述制备的有效膜面积为9cm2的镍黑-石墨烯复合光热转换膜置于装有浓度为30g/L NaCl溶液的蒸发杯上,采用光强度为1sun的模拟太阳光进行照射。称取蒸发杯的初始重量和结束重量,进行蒸汽渗透率的计算。The nickel black-graphene composite light-to-heat conversion film prepared above with an effective film area of 9 cm2 was placed on an evaporation cup with a concentration of 30 g/L NaCl solution, and was irradiated with simulated sunlight with a light intensity of 1 sun. Weigh the initial weight and end weight of the evaporation cup to calculate the vapor permeability.
实施例1Example 1
将1.32g的硫酸铵和0.42g的硫酸镍加200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将泡沫镍接在阴极上,石墨箔接在阳极上,将接好的电极调整好距离并放入电解液中;打开外加直流电源的开关,13V电压下反应10分钟;将镀好的镍黑-石墨烯光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。在1sun的光照下置于蒸发杯上,光-蒸汽能量转化效率为136.94%,蒸汽渗透率为2.00 kg/m2·h。Add 1.32g of ammonium sulfate and 0.42g of nickel sulfate to 200ml of deionized water, and keep stirring at room temperature until fully dissolved to form an electrolyte solution; connect the foamed nickel to the cathode and the graphite foil to the anode, and connect the connected Adjust the electrode distance and put it into the electrolyte; turn on the switch of the external DC power supply, and react at 13V for 10 minutes; wash the plated nickel black-graphene light-to-heat conversion film in deionized water, take it out and bake it in an oven at 60°C Let dry for 12 hours. Placed on the evaporation cup under the light of 1 sun, the light-steam energy conversion efficiency is 136.94%, and the vapor permeability is 2.00 kg/m 2 ·h.
实施例2Example 2
将1.32g的硫酸铵和0.42g的硫酸镍加200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将泡沫镍接在阴极上,石墨箔接在阳极上,将接好的电极调整好距离并放入电解液中;打开外加直流电源的开关,13V电压下反应20分钟;将镀好的镍黑-石墨烯光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。在1sun的光照下置于蒸发杯上,光-蒸汽能量转化效率为138.49%,蒸汽渗透率为2.02 kg/m2·h。Add 1.32g of ammonium sulfate and 0.42g of nickel sulfate to 200ml of deionized water, and keep stirring at room temperature until fully dissolved to form an electrolyte solution; connect the foamed nickel to the cathode and the graphite foil to the anode, and connect the connected Adjust the electrode distance and put it into the electrolyte; turn on the switch of the external DC power supply, and react at 13V for 20 minutes; wash the plated nickel black-graphene photothermal conversion film in deionized water, take it out and bake it in an oven at 60°C Let dry for 12 hours. Placed on the evaporation cup under the light of 1 sun, the light-steam energy conversion efficiency is 138.49%, and the vapor permeability is 2.02 kg/m 2 ·h.
实施例3Example 3
将1.32g的硫酸铵和0.42g的硫酸镍加200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将泡沫镍接在阴极上,石墨箔接在阳极上,将接好的电极调整好距离并放入电解液中;打开外加直流电源的开关,13V电压下反应30分钟;将镀好的镍黑-石墨烯光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。在1sun的光照下置于蒸发杯上,光-蒸汽能量转化效率为162.48%,蒸汽渗透率为2.37 kg/m2·h。Add 1.32g of ammonium sulfate and 0.42g of nickel sulfate to 200ml of deionized water, and keep stirring at room temperature until fully dissolved to form an electrolyte solution; connect the foamed nickel to the cathode and the graphite foil to the anode, and connect the connected Adjust the distance between the electrodes and put them into the electrolyte; turn on the switch of the external DC power supply, and react at 13V for 30 minutes; wash the plated nickel black-graphene light-to-heat conversion film in deionized water, take it out and bake it in an oven at 60°C Let dry for 12 hours. Placed on the evaporation cup under the light of 1 sun, the light-steam energy conversion efficiency is 162.48%, and the vapor permeability is 2.37 kg/m 2 ·h.
实施例4Example 4
将1.32g的硫酸铵和0.42g的硫酸镍加200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将泡沫镍接在阴极上,石墨箔接在阳极上,将接好的电极调整好距离并放入电解液中;打开外加直流电源的开关,13V电压下反应40分钟;将镀好的镍黑-石墨烯光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。在1sun的光照下置于蒸发杯上,光-蒸汽能量转化效率为140.37%,蒸汽渗透率为2.05 kg/m2·h。Add 1.32g of ammonium sulfate and 0.42g of nickel sulfate to 200ml of deionized water, and keep stirring at room temperature until fully dissolved to form an electrolyte solution; connect the foamed nickel to the cathode and the graphite foil to the anode, and connect the connected Adjust the distance between the electrodes and put them into the electrolyte; turn on the switch of the external DC power supply, and react at 13V for 40 minutes; wash the plated nickel black-graphene photothermal conversion film in deionized water, take it out and bake it in an oven at 60°C Let dry for 12 hours. Placed on the evaporation cup under the light of 1 sun, the light-vapor energy conversion efficiency is 140.37%, and the vapor permeability is 2.05 kg/m 2 ·h.
对比例 1:Comparative example 1:
将装有浓度为30g/L NaCl溶液的不放膜的蒸发杯,采用光强度为1sun的模拟太阳光进行照射。称取蒸发杯的初始重量和结束重量,计算光-蒸汽能量转化效率为50.89%,蒸汽渗透率为0.75k g/m2·h。Irradiate the evaporation cup with a concentration of 30g/L NaCl solution without a film on it with simulated sunlight with a light intensity of 1 sun. The initial weight and end weight of the evaporation cup were weighed, and the light-to-steam energy conversion efficiency was calculated to be 50.89%, and the vapor permeability was 0.75k g/m 2 ·h.
对比例 2:Comparative example 2:
将1.32g的硫酸铵加入200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将泡沫镍接在阴极上,两块镍板接分别接在泡沫镍左右两侧的阳极上,将接好的电极调整好距离并放入电解液中;打开外加直流电源,15V电压下电解20分钟;将镀好的镍黑光热转换膜在去离子水中清洗,取出后60℃烘箱烘干12小时。在1sun的光照下,光-蒸汽能量转化效率为91.87%,蒸汽渗透率为1.07kg/m2·h。Add 1.32g of ammonium sulfate to 200ml of deionized water, and continue to stir at room temperature until fully dissolved to form an electrolyte solution; connect the foamed nickel to the cathode, and connect the two nickel plates to the anodes on the left and right sides of the foamed nickel respectively. Adjust the distance between the connected electrodes and put them into the electrolyte; turn on the external DC power supply and electrolyze for 20 minutes at 15V; wash the plated nickel black light-to-heat conversion film in deionized water, take it out and dry it in an oven at 60°C 12 hours. Under the light of 1 sun, the light-steam energy conversion efficiency is 91.87%, and the vapor permeability is 1.07kg/m 2 ·h.
对比例 3:Comparative example 3:
将1.32g的硫酸铵加入200ml去离子水中,在室温下持续搅拌至充分溶解,形成电解质溶液;将阴极阳极分别放上石墨箔,剥离1小时后,将所得的石墨烯抽滤成石墨烯膜。在1sun的光照下,光-蒸汽能量转化效率为81.20%,蒸汽渗透率为1.19kg/m2·h。Add 1.32g of ammonium sulfate into 200ml of deionized water, and continue to stir at room temperature until fully dissolved to form an electrolyte solution; put graphite foil on the cathode and anode respectively, and after peeling off for 1 hour, the obtained graphene is suction-filtered into a graphene film . Under the light of 1 sun, the light-steam energy conversion efficiency is 81.20%, and the vapor permeability is 1.19kg/m 2 ·h.
结论:in conclusion:
通过表1可以看出,与镍黑膜和石墨烯膜对比,镍黑-石墨烯复合光热转换膜实现了协同促进的作用,在海水淡化中具有较好的作用,且电解时间为30min时膜的光-蒸汽能量转化效率和蒸汽渗透率最大。It can be seen from Table 1 that compared with nickel black film and graphene film, nickel black-graphene composite light-to-heat conversion film has achieved a synergistic promotion effect, and has a better effect in seawater desalination, and the electrolysis time is 30min The light-to-vapor energy conversion efficiency and vapor permeability of the film are maximized.
表1 有效膜面积为9cm2的镍黑-石墨烯复合光热转换膜及对比例在1sun光照下的蒸汽渗透率Table 1 The vapor permeability of nickel black-graphene composite light-to-heat conversion film with an effective film area of 9 cm 2 and the comparative example under 1 sun light
Claims (3)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202111047273.8A CN113772664B (en) | 2021-09-08 | 2021-09-08 | Nickel black-graphene composite photo-thermal conversion film and preparation method thereof |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202111047273.8A CN113772664B (en) | 2021-09-08 | 2021-09-08 | Nickel black-graphene composite photo-thermal conversion film and preparation method thereof |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN113772664A CN113772664A (en) | 2021-12-10 |
| CN113772664B true CN113772664B (en) | 2023-04-28 |
Family
ID=78841484
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN202111047273.8A Active CN113772664B (en) | 2021-09-08 | 2021-09-08 | Nickel black-graphene composite photo-thermal conversion film and preparation method thereof |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN113772664B (en) |
Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN108862254A (en) * | 2018-07-12 | 2018-11-23 | 西安交通大学 | A kind of method that the bipolar electrode removing of electrochemistry yin-yang prepares graphene |
Family Cites Families (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104505497B (en) * | 2014-12-12 | 2017-01-04 | 盐城市新能源化学储能与动力电源研究中心 | Graphene nickel electrode prepared by a kind of Graphene nickel composite material and this material of use |
| CN104817143B (en) * | 2015-04-05 | 2018-02-23 | 北京化工大学 | Amberplex multiple multipole capacitive adsorption desalter |
| CN106803461A (en) * | 2015-11-26 | 2017-06-06 | 常德力元新材料有限责任公司 | Directly soak the three-dimensional porous electrode preparation method of nickel foam-Graphene of reaction equation |
| EP3417092B1 (en) * | 2016-02-17 | 2023-07-26 | Power Resources Group Ltd | Methods of making graphene materials |
| CN106276878A (en) * | 2016-08-16 | 2017-01-04 | 肖丽芳 | A kind of electrodeposition process prepares the method for grapheme foam |
| CN113292140A (en) * | 2021-06-28 | 2021-08-24 | 长春工业大学 | Preparation method and application of nitrogen-doped titanium dioxide particle-loaded graphene-nickel foam membrane electrode |
-
2021
- 2021-09-08 CN CN202111047273.8A patent/CN113772664B/en active Active
Patent Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN108862254A (en) * | 2018-07-12 | 2018-11-23 | 西安交通大学 | A kind of method that the bipolar electrode removing of electrochemistry yin-yang prepares graphene |
Also Published As
| Publication number | Publication date |
|---|---|
| CN113772664A (en) | 2021-12-10 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN111962083B (en) | Preparation method and application of graphene roll-coated graphite-phase carbon nitride nanotube photoelectrode | |
| CN101950605B (en) | Technology for obtaining porous high-purity anatase phase titanium dioxide film on surface of flexible matrix material | |
| CN110124687A (en) | A kind of preparation method of the LDH/rGO composite material of ruthenium doping and its application on evolving hydrogen reaction | |
| CN106087002A (en) | A kind of 3D structure Ni/rGO is combined the preparation method of hydrogen-precipitating electrode | |
| CN106350849B (en) | Electrodeposition preparation method of oxide film on aluminum surface with high absorption and low emission solar spectrum | |
| CN106319558B (en) | A kind of MoS of high-efficiency multiple2- Zn hydrogen-precipitating electrodes and preparation method thereof | |
| CN106732669A (en) | A kind of MoS as photoelectrocatalysis liberation of hydrogen material2/In2S3Composite catalyst and preparation method thereof | |
| CN107093703A (en) | A kind of preparation method of manganese dioxide/foam copper sodium-ion battery self-supporting negative pole | |
| CN105696014B (en) | A kind of nitrogen-doped graphene N-rGO and nanoscale twins cluster MoSe2Composite construction and preparation method | |
| CN113637986A (en) | Dual-phase nickel selenide bifunctional catalyst for electrolysis of water and its preparation method and application | |
| CN106391079A (en) | Preparation method of g-C3N4 film for photoelectrocatalysis hydrolysis | |
| CN114899385B (en) | Carbon/manganese dioxide composite material and its preparation method and application | |
| CN106955689A (en) | A kind of preparation method of redox graphene/cuprous oxide composite photo-catalyst | |
| CN106591914A (en) | Copper, indium, selenium and sulfur thin film solar cell absorbing layer prepared through electrodeposition method | |
| CN102544375B (en) | Wide-spectral-response flexible photo-anode of solar cell and manufacturing method of wide-spectral-response flexible photo-anode | |
| CN114686944A (en) | Surface treatment method for reducing oxygen-free copper secondary electron yield | |
| CN106011958B (en) | A kind of cupromanganese plating solution and its application for being used to prepare copper galaxite coating | |
| CN113818064B (en) | Needle-shaped nickel black film capable of realizing efficient photo-thermal conversion | |
| CN115466986B (en) | Electrode for producing hydrogen by waste water electrolysis and preparation method and application thereof | |
| CN110965074A (en) | Method for preparing composite film photoelectrode | |
| CN113772664A (en) | Nickel black-graphene composite photo-thermal conversion film and preparation method thereof | |
| CN113289622B (en) | A water splitting hydrogen production composite material and its preparation method | |
| CN114059078B (en) | A kind of preparation method of piezoelectric enhanced photoelectric catalyst | |
| CN110589818B (en) | Preparation method and application of nitrogen-doped mesoporous carbon material | |
| CN105803482A (en) | Modification method for collector electrode material of electrolytic cell for water-electrolytic hydrogen making, and application |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| GR01 | Patent grant | ||
| GR01 | Patent grant | ||
| TR01 | Transfer of patent right | ||
| TR01 | Transfer of patent right |
Effective date of registration: 20260113 Address after: 130000 Jilin Province, Changchun City, Erdao District, Yandada Street and Hugong Road Intersection, Changchun Northeast Asia International Procurement Center B1-35 Patentee after: Jilin Wensheng New Materials Co.,Ltd. Country or region after: China Address before: 130012 Yanan street, Jilin, Chaoyang District, No. 2055, No. Patentee before: Changchun University of Technology Country or region before: China |
